Adaptive MLP Network Reference Model for Controlling Flow of Split Level Coupled Tank - Samer Sherif Kassem, Samer Sherif (2010)
This draft report explains about the background of tank systems such as the single tank system as well as the split coupled tank and how to model such tanks using Simulink blocks.